2009
DOI: 10.1111/j.1399-3038.2009.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy after liver transplantation in children: a prospective study

Abstract: Food allergy has been increasingly reported in children who had orthotopic liver transplantation (OLT). We aimed to conduct a prospective study to investigate the prevalence of sensitizations and food allergy in pediatric OLT recipients. We also aimed to identify potential risk factors. The study group consisted of 28 children (14 male, 14 female, mean age 4.96 +/- 0.76 yrs) who had OLT. Total eosinophil count (TEC), total IgE, and specific IgEs were studied before and 3, 6, 12 months after OLT. Six patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
62
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 18 publications
9
62
1
Order By: Relevance
“…Through this retrospective study, the incidence of new-onset food allergy in adult patients after CBT was estimated to be 6.6%. This incidence was lower than that reported in liver transplantation (10-21%) 3,4 and seemed higher than the estimated rate of 0.2-0.6% in common food allergies in the adult population, such as those against milk, egg, wheat and peanuts. 10 It is notable that food allergy associated with liver transplantation has been reported exclusively in pediatric patients.…”
contrasting
confidence: 40%
See 4 more Smart Citations
“…Through this retrospective study, the incidence of new-onset food allergy in adult patients after CBT was estimated to be 6.6%. This incidence was lower than that reported in liver transplantation (10-21%) 3,4 and seemed higher than the estimated rate of 0.2-0.6% in common food allergies in the adult population, such as those against milk, egg, wheat and peanuts. 10 It is notable that food allergy associated with liver transplantation has been reported exclusively in pediatric patients.…”
contrasting
confidence: 40%
“…10 It is notable that food allergy associated with liver transplantation has been reported exclusively in pediatric patients. [1][2][3][4] However, our study showed that adult patients can also develop food allergy after CBT. Indeed, two adult cases of food allergy after CBT have recently been reported.…”
mentioning
confidence: 61%
See 3 more Smart Citations